Curie temperatures of titanomagnetite in ignimbrites: Effects of emplacement temperatures, cooling rates, exsolution, and cation ordering - (:unkn) unknown (My University, 2014)
Pumices, ashes, and tuffs from Mt. St. Helens and from Novarupta contain two principal forms of titanomagnetite: homogeneous grains with Curie temperatures in the range 350–500°C and oxyexsolved grains with similar bulk composition, containing ilmenite lamellae and having Curie temperatures above 500°C. Thermomagnetic analyses and isothermal annealing experiments in combination with stratigraphic settings and thermal models show that emplacement temperatures and cooling history may have affected the relative proportions of homogeneous and exsolved grains and have clearly had a strong influence on the Curie temperature of the homogeneous phase. The exsolved grains are most common where emplacement temperatures exceeded 600°C, and in laboratory experiments, heating to over 600°C in air causes the homogeneous titanomagnetites to oxyexsolve rapidly. Where emplacement temperatures were lower, Curie temperatures of the homogeneous grains are systematically related to overburden thickness and cooling timescales, and thermomagnetic curves are generally irreversible, with lower Curie temperatures measured during cooling, but little or no change is observed in room temperature susceptibility. We interpret this irreversible behavior as reflecting variations in the degree of cation ordering in the titanomagnetites, although we cannot conclusively rule out an alternative interpretation involving fine-scale subsolvus unmixing. Shortrange ordering within the octahedral sites may play a key role in the observed phenomena. Changes in the Curie temperature have important implications for the acquisition, stabilization, and retention of natural remanence and may in some cases enable quantification of the emplacement temperatures or cooling rates of volcanic units containing homogeneous titanomagnetites.